Periodic assignment: Exploring students' perception and their academic achievement - Adnan, Husnul Khatimah; Jannah, Miftahul; Razali, Khairil (English Dapartment, Faculty of Languages and Arts, Universitas Negeri Semarang, 2020)
Determining the perception of English Department students toward the periodic assignment and how it develops students' academic achievement was the aim of this study. The correspondents were 42 students who experienced periodic assignments in English for Academic Purposes subject at English Department of UIN Ar-Raniry, Banda Aceh. This study used a quatitative descriptive research design. The data were collected through questionnaires as the researcher used a four-point Likert scale questionnaire adapted from Turanli (2009) as the instrument. The scale was taken for exploring respondents' personality. Frequency distribution was used to analyze the obtained data and it would be presented in percentage. From 16 questions, the findings revealed that many students expressed positive perception towards periodic assignments in learning English for Academic Purposes. The students also expressed that the periodic assignments had developed their academic achievement. This study was not only useful for teachers' practical teaching, but it provided the base for future research about periodic assignment.